Pengaruh Rasio Profitabilitas Dan Rasio Pasar Terhadap Return Saham (Studi Empiris pada Perusahaan Manufaktur Sektor Food and Baverage Periode 2003-2012) - Faizin, Faizin; , Drs. Sri Padmantyo, MBA (2016)
The capital market has a strategic role as a source of financing for businesses and investment vehicles for investors. Before investing, investors need to make sure whether the invested capital is able to provide the level of expected return or not, that is by knowing the company's performance. It required an assessment of the performance of the companies that will be used as a place for investment. This can be done by analyzing the financial statements of the company concerned, as the financial statements are a reflection of the achievements of management of a company at a certain period. This study aims to reveal how influence profitability ratios (EPS, ROA, ROE, NPM) and the market ratio (PER and PBV) either partially or simultaneously to return stock at food and beverage companies listed on the Stock Exchange 2003-2012 period. The population which is the object of this research is a food and beverage company in the period 2003-2012. The samples used were 15 companies manufacturing food and beverage sector and still stand for a period of perception and also published in 2003-2012 and selected by purposive sampling. The analytical method used in this research is the multiple regression analysis to obtain a comprehensive picture of the relationship between the variables and the other variables. T test research results showed that the only variable ROE and PBV have a significant influence on stock return, while variable EPS, ROA, NPM and PER do not have a significant effect on stock returns. Likewise from F test results indicate that the EPS, ROA, ROE, NPM, PER and PBV simultaneously (together) effect on stock returns.